2002
DOI: 10.1524/ract.2002.90.5_2002.289
|View full text |Cite
|
Sign up to set email alerts
|

Complexation and luminescence spectroscopic studies of europium(III) with polymaleic acid

Abstract: Eu / Polycarboxylic acid / Complexation / Laser spectroscopySummary. The complexation behavior of europium(III) with polymaleic acid (PMA) was studied at pH 5 in 0.1 M NaClO 4 by anion exchange (AE). The concentration range investigated was from 10 −9 M to 10 −4 M for the europium ion and from 1 to 50 mg/l for the polymer. The quantitative description of experimental data showed the formation of a 1 : 1 Eu : PMA complex and the existence of at least two distinct interaction environments ("sites") of Eu with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…7A) considering only one species as observed by Kubota et al [1]. The conditional constant obtained at pH 5 (log K app = 6.65) is comparable with the values given in the literature and determined using the anionic exchange separation method (log K app = 6.23) [2] or the displacement method based on a liquid/liquid separation procedure (log K app = 7.06) [1]. The one deduced from the displacement method using a solid/liquid separation methodology appears therefore underestimated (log K app = 5.24) [3].…”
Section: Quantitative Description Of Complexation Datasupporting
confidence: 88%
See 3 more Smart Citations
“…7A) considering only one species as observed by Kubota et al [1]. The conditional constant obtained at pH 5 (log K app = 6.65) is comparable with the values given in the literature and determined using the anionic exchange separation method (log K app = 6.23) [2] or the displacement method based on a liquid/liquid separation procedure (log K app = 7.06) [1]. The one deduced from the displacement method using a solid/liquid separation methodology appears therefore underestimated (log K app = 5.24) [3].…”
Section: Quantitative Description Of Complexation Datasupporting
confidence: 88%
“…According to the model, to ensure balanced charges within the gel phase, three positive charges need to be compensated by three negative charges. It was experimentally shown that at saturation, the number of bound metal ions corresponds to the number of deprotonated carboxylic groups determined by potentiometric titration [2,7]. This appears coherent with an ion exchange model.…”
Section: Quantitative Description Of Complexation Datamentioning
confidence: 52%
See 2 more Smart Citations
“…The degree of PAA loading, corresponding to the ratio between concentrations of sorbed PAA (in mg/L) and of alumina (in g/L), was equal to Γ=59±3 mg/g. This value corresponds to the maximum of adsorption deduced from isotherm data [23]. Under these conditions, the alumina surface is saturated by PAA.…”
Section: Introductionmentioning
confidence: 51%